Patterns of proton therapy use in pediatric cancer management in 2016: An international survey - Journy, Neige; Indelicato, Daniel J; Withrow, Diana R; Akimoto, Tetsuo; Alapetite, Claire; Araya, Masayuki; Chang, Andrew; Chang, John Han-Chih; Chon, Brian; Confer, Michael E; Demizu, Yusuke; Dendale, Rémi; et al. (Radiotherapy and oncology, 2019)
PURPOSE: To facilitate the initiation of observational studies on late effects of proton therapy in pediatric patients, we report on current patterns of proton therapy use worldwide in patients aged less than 22 years. MATERIALS & METHODS: Fifty-four proton centers treating pediatric patients in 2016 in 11 countries were invited to respond to a survey about the number of patients treated during that year by age group, intent of treatment, delivery technique and tumor types. RESULTS: Among the 40 participating centers (participation rate: 74%), a total of 1,860 patients were treated in 2016 (North America: 1205, Europe: 432, Asia: 223). The numbers of patients per center ranged from 1 to 206 (median: 29). Twenty-four percent of the patients were <5 years of age, and 50% <10 years. More than 30 pediatric tumor types were identified, mainly treated with curative intent: 48% were CNS, 25% extra-cranial sarcomas, 7% neuroblastoma, and 5% hematopoietic tumors. About half of the patients were treated with pencil beam scanning. Treatment patterns were broadly similar across the three continents. CONCLUSION: To our knowledge, this survey provides the first worldwide assessment of proton therapy use for pediatric cancer management. Since previous estimates in the United States and Europe, CNS tumors remain the cancer types most commonly treated with protons in 2016. However, the proportion of extra-cranial tumors is growing worldwide. The typically low numbers of patients treated in each center indicate the need for international research collaborations to assess long-term outcomes of proton therapy in pediatric patients.
Keywords: Young Adult; Male; Child, Preschool; Neoplasms; mladý dospělý; Adolescent; celková dávka radioterapie; Infant; Child; dítě; Adult; Proton Therapy; dospělí; mužské pohlaví; Pediatrics; průzkumy a dotazníky; mladiství; Radiotherapy Dosage; předškolní dítě; lidé; ženské pohlaví; Humans; kojenec; nádory; protonová terapie; pediatrie; Female; Surveys and Questionnaires